AN INTEGRATED APPROACH TO THE DIAGNOSIS OF OPTIC NERVE ABNORMALITIES: FROM CLINICAL OBSERVATIONS TO INNOVATIVE TECHNIQUES (REVIEW ARTICLE) - Bilalov E.N.; Нарзикулова К.И.; Zakirkhodjaev R.A.; Oralov B.A.; Asorkhozhaeva I.R. (Western European Studies, 2024)
In recent decades, the attention of specialists has been increasingly focused on the problem of abnormalities in the development of the optic nerve [1, 7, 14], which is due to their significant impact on visual function and quality of life of patients. Developmental abnormalities of the optic nerve, including optic disc coloboma, cavernous anomaly, and others, are complex and diverse in nature. These can range from minor abnormalities with little to no effect on vision to serious conditions leading to significant visual impairment or even blindness
Keywords: vision; impairment; blindness; optic